Sleep bruxism in children and its association with clinical and sleep characteristics: cross-sectional study - ALVES,Eliezer Gomes (2022)
ABSTRACT Objective: The aim of the present study was to evaluate the prevalence of bruxism in children and its association with clinical and sleep characteristics. Methods: The study sample composed of 239 children aged 7 to 10 years enrolled in a public and a private school in the city of São Luís (MA). Bruxism was investigated based on parental reports of teeth grinding at night, sleep quality, and both intraoral and extraoral clinical aspects related to the condition. Data analysis involved descriptive statistics, Pearson’s chi-squared (c2) test, the linear trend c2 test, and Fisher’s exact test with a 5% significance level. Results: The prevalence of bruxism was 19.7%. Among the children with bruxism, 17% had poor sleep quality, 44.1% slept up to nine hours per night, 82.2% had daytime sleepiness, and 17.9% felt tiredness or pain in the facial muscles upon waking. Conclusions: Based on the present findings, the prevalence of sleep bruxism was significant. No significant associations were observed with the factors investigated, although daytime sleepiness was found to be the most prevalent characteristic of bruxism.